Association of Systemic Lupus Erythematosus With Decreased Immunosuppressive Potential of the IgG Glycome. Issue 11 (November 2015) - Vučković, Frano; Krištić, Jasminka; Gudelj, Ivan; Teruel, Maria; Keser, Toma; Pezer, Marija; Pučić‐Baković, Maja; Štambuk, Jerko; Trbojević‐Akmačić, Irena; Barrios, Clara; Pavić, Tamara; Menni, Cristina; et al.
Abstract : Objective: Glycans attached to the Fc portion of IgG are important modulators of IgG effector functions. Interindividual differences in IgG glycome composition are large and they associate strongly with different inflammatory and autoimmune diseases. IKZF1, HLA–DQ2A/B, and BACH2 genetic loci that affect IgG glycome composition show pleiotropy with systemic lupus erythematosus (SLE), indicating a potentially causative role of aberrant IgG glycosylation in SLE. We undertook this large multicenter case–control study to determine whether SLE is associated with altered IgG glycosylation. Methods: Using ultra‐performance liquid chromatography analysis of released glycans, we analyzed the composition of the IgG glycome in 261 SLE patients and 247 matched controls of Latin American Mestizo origin (the discovery cohort) and in 2 independent replication cohorts of different ethnicity (108 SLE patients and 193 controls from Trinidad, and 106 SLE patients and 105 controls from China). Results: Multiple statistically significant differences in IgG glycome composition were observed between patients and controls. The most significant changes included decreased galactosylation and sialylation of IgG (which regulate proinflammatory and antiinflammatory actions of IgG) as well as decreased core fucose and increased bisecting N ‐acetylglucosamine (which affect antibody‐dependent cell‐mediated cytotoxicity). Conclusion: The IgG glycome in SLE patients is significantly altered in a way that decreases immunosuppressive action of circulating immunoglobulins. The magnitude of observed changes is associated with the intensity of the disease, indicating that aberrant IgG glycome composition or changes in IgG glycosylation may be an important molecular mechanism in SLE.